EDTA-enhanced alkaline anaerobic fermentation of landfill leachate-derived waste activated sludge for short-chain fatty acids production: Metals chelation and EPSs destruction. (15th May 2023) - Luo, Jinghuan; Jiang, Li; Wei, Yuanyuan; Li, Yanmei; Yang, Guiyu; Li, Yu-You; Liu, Jianyong
Abstract: Alkaline anaerobic fermentation (AAF) of waste activated sludge (WAS) has been demonstrated to be promising for short-chain fatty acids (SCFAs) recovery. However, high-strength metals and EPSs in the landfill leachate-derived WAS (LL-WAS) would stabilize its structure, suppressing AAF performance. To improve sludge solubilization and SCFAs production, AAF was coupled with EDTA addition for LL-WAS treatment. The results show that sludge solubilization at AAF-EDTA was promoted by 62.8% than AAF, releasing 21.8% more soluble COD. The maximal SCFAs production of 477.4 mg COD/g VSS was thus achieved, i.e., 1.21 and 6.13 times those at AAF and the control, respectively. SCFAs composition was also improved with more acetic and propionic acids (80.8% versus 64.3%). Metals bridging EPSs were chelated by EDTA, which significantly dissolved metals from sludge matrix (e.g., 23.28 times higher soluble Ca than AAF). EPSs tightly bound with microbial cells were thus destructed (e.g., 4.72 times more protein release than alkaline treatment), causing an easier sludge disruption and subsequently a higher SCFAs production by hydroxide ions. These findings suggest an effective EDTA-supported AAF for metals and EPSs-rich WAS to recover carbon source. Graphical abstract: Image 1 Highlights: EDTA addition was proposed to enhance AAF of metals and EPSs-rich LL-WAS. Sludge solubilization was promoted by 62.8%, releasing 21.8% more SCOD than AAF. SCFAs production of AAF-EDTA were 1.21 and 6.13 times of AAF and the control. SCFAs composition was improved from AAF with 25.7% more acetic and propionic acids. EDTA largely chelated metals from sludge matrix, causing EPSs destruction.